Emergence of Rickettsia africae, Oceania - Eldin, Carole (Centers for Disease Control and Prevention, 2011)
We detected Rickettsia africae, the agent of African tick-bite fever (ATBF), by amplification of fragments of gltA, ompA, and ompB genes from 3 specimens of Amblyomma loculosum ticks collected from humans and birds in New Caledonia. Clinicians who treat persons in this region should be on alert for ATBF.